Understanding the relationship between socioeconomic status, language and educational achievment: |a critical analysis - Evans, Lorna. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 1983., 1983)
This study draws on literature from English speaking countries to explore the relationship between social class, lanouage and educational achievment. It refers specifically to societies where differences within the common language and between social classes seem to predispose certain children to educational failure. The study finds a concensus of opinion that membership of a particular social class influences the dialect, or variety of language, acquired by the young child. The different socialisin0 orocess experienced by children of different socioeconomic status are commonly held to be responsible for this ohenomenon. The research indicates that the child of low socioeconomic status performs less well in school than his higher socioeconomic status counterpart, due to the child usinq a dialect which does not correspond with the language used in school. This study explores the possibility that other factors may account for that poor educational performance of the low socio-economic status child. Recent research indiactes that this poor academic performance may be attributable to a multitudel,of factors. It may be that dialect llsed by the low soci oeconomic status ch ild does not refl ect the accepted values and thought pattern esteemed by the middle-class oriented academic environments. Likewise, it may not be any instrinsic quality in the child's dialect that disenables him, but rather either people's reactions to it, which may be negative, or the inconsequence between the values reflected by the child's language and his expression style. The low prestige accorded to nonstandard dialects is often extended to those who use such dialects and the low exoectatations of teachers for such children may become a selffulfilling prophecy. Society is becoming increasinqly aware of the problems of the low socioeconomic status child, and is instituting programmes both general and language specific, to help him. This study makes a critical analysis of some of the latter programmes. It finds that although the aims of programmes still vary from el iminatinq nonstandard dialects to fostering only nonstandard dialects, educators are learnina from nast exoeriences how best to develop programmes which will fully benefit the youna child. Its conclusion is one of hope, for with increased knowledqe and commitment, the educational future of the low socio-economic status child must surely improve.
Keywords: Social status.; Academic achievement.; Social indicators.; Language and culture.